Preparation of Bioethanol from Pineapple Peel Waste for Blending Pertalite into Alternative Fuel (Gasohol) - Ihtifazhuddin, Farhan; Yerizam, Muhammad; Yuliati, Selastia (Jurnal Sumberdaya Alam dan Lingkungan, 2024)
This study aims to obtain bioethanol according to the Indonesian National Standard (SNI) 7390:2012, obtain Gasohol according to the RON (Research Octane Number) standard in Pertalite, and produce alternative fuels that are more environmentally friendly. The bioethanol production process includes hydrolysis, fermentation, distillation, and adsorption, with Saccharomyces cerevisiae to ferment sugar in pineapple skin into ethanol with a content of 59.62% from a 5-day fermentation process with 4% Saccharomyces cerevisiae, 0.5% urea, 0.5% NPK. Bioethanol is then mixed with Pertalite in the composition of E5 (5 ml of bioethanol mixed with 95 ml of Pertalite) to E25 (25 ml of bioethanol mixed with 75 ml of Pertalite), lowering the flash point of the mixture from 29.8°C (E5) to 28.0°C (E25), increasing the density from 0.7239 gr.(cm3)-1 (E5) to 0.7250 gr.(cm3)-1 (E25) and the viscosity from 0.41 cSt (E5) to 0.49 cSt (E25). Still, the octane number (RON) tends to be stable at 91.4-95.6. As a result, the bioethanol content is close to SNI 99.5%, the bioethanol-Pertalite mixture improves several parameters but lowers the flash point, and the E25 mixture meets the RON standard of 95.6 for Pertalite.